First-principles study on linear and nonlinear optical properties of ZnGeP2 - 肖瑞春 吴海信 倪友保 王振友 黄昌保 程旭东 (中国物理B：英文版, 2015)
The study of the linear and nonlinear optical properties of Zn Ge P2 based on density functional theory has been carried out. In order to get a more physical picture in the infrared region, terms which are considered as the phonon effect were added to the calculated refractive dispersion curves. The phonon-corrected calculation curves show excellent agreement with experimental refractive indexes, which gives a better comprehension of the linear optical proprieties in the transparent region. The static nonlinear optical susceptibility was investigated using approaches based on the ＂sum over states＂ and the2 n ＋ 1 theorem methods. Both of the results of these two methods reasonably coincided with the experimental results.